Innowacyjność a konkurencyjność gospodarki turystycznej - Januszewska, Małgorzata (Innovation vs. Competitiveness of Tourist Economy, 2008)
The basis for establishing a competitive tourist enterprise becomes an attitude according to which there is a direct relation between a long lasting and solid competitive advantage of an enterprise and its innovation. Such an advantage stems mainly from the sets of defined and specific resources, skills and structures of an enterprise. The objective of the hereby article is to present how indispensable innovative activities in constructing a competitive profile of a tourist enterprise are. The article presents the innovation attributes and sources of a tourist enterprise and how to create an analytical scheme defining the relation between the innovation and competitiveness of an enterprise. The article is summed up by conclusions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 29, s. 68-77